Competency Assessment as a Way of Determining Training and Educational Needs of Extension Professionals in Nepal - Ramjee P. Ghimire; Murari Suvedi; Michael Kaplowitz; Robert Richardson (Journal of International Agricultural and Extension Education, 2017)
This study examines the level of and gaps in core competencies among agricultural extension professionals in Nepal. The study population was composed of agricultural extension professionals in governmental extension offices and agriculture-based, non-governmental organizations. During August-September 2015, 349 extension professionals completed selfadministered surveys. The design for the data collection instrument was based on a literature review and on focus group recommendations. Data were analyzed using descriptive and inferential statistics. The findings revealed that respondents perceived themselves to be moderately competent in extension core competencies – program planning, program implementation, communication skills, educational and informational technology, program evaluation, personal and professional development, diversity, and technical subject matter expertise. Respondents’ perceived levels of competency differed by their current position, undergraduate college attended, and level of education, although not much by their age and experience in extension. Office chiefs and foreign-educated respondents perceived themselves as having higher levels of competency than their counterparts – subject matter specialists and technical officers, and in-country-educated professionals. The perceived levels of the importance of all core competencies were significantly higher than the professionals’ perceived levels of their own competency, indicating gaps in extension core competencies among Nepalese extension professionals. The findings imply that that there is a need for in-service training of extension professionals in all core competency areas. Preservice extension education curricula need to be reviewed and updated, incorporating the core competencies highlighted in this study.
Keywords: agricultural extension professionals; extension core competencies; levels of core competency; competency assessment; Nepal